Review Jurnal: Efektivitas Penggunaan Kuning Telur Berbagai Jenis Unggas Sebagai Pengencer Semen pada Ternak: Literature Review: Effectiveness of Using Egg Yolks of Various Types of Poultry as a Semen Diluent in Cattle - Rizky, Dinda Khalifa; Ridlo, Muhammad Rosyid; Khotimah, Anisatun Khusnul; Bidaraswati, Arsy (Jurnal Ilmiah Ilmu-Ilmu Peternakan, 2023)
A method is needed that can be used to maintain sperm quality in order to produce superior seeds. The use of poultry egg yolk as a diluent is of course widely used because poultry eggs can maintain the good quality of cattle sperm. This research aims to determine the level of effectiveness of egg yolks of various types of poultry as a sperm diluent on the motility and viability of cattle sperm. The method used in this research is the literature review method and the descriptive method. The results showed that the use of free-range chicken egg yolk and quail egg yolk as sperm diluent showed the highest motility values. The highest percentage of viability was in purebred chickens, while the lowest abnormality was in dilution with goose yolk eggs.